A Novel Optimization Algorithm based on the Natural Behavior of the Ant Colonies - Jiraporn Kiatwuthiamorn; Arit Thammano (My University, 2013)
Optimization problem is one of the most challenging problems that has received considerable attention over the last decade. Many metaheuristic methods have been proposed and successfully applied to find the optimal solution. Each technique has its good and bad points. A new optimization technique based on the natural behavior of the ant colonies is proposed in this paper. In this proposed algorithm, the foraging behavior of worker ants is employed for locally searching for better solution while the marriage, breeding, and feeding behaviors are used in reproduction of the new generation. The proposed algorithm has been evaluated on several benchmark problems. The experimental results demonstrate the effectiveness of the proposed algorithm.
Keywords: Benchmark (surveying); Optimization algorithm; Swarm intelligence; Parallel metaheuristic; Metaheuristic Optimization Algorithms Research